Andrographis paniculata improves glucose regulation by enhancing insulin sensitivity and upregulating GLUT 4 expression in Wistar rats - Saka, W. A.; Oyekunle, O. S.; Akhigbe, T. M.; Oladipo, O. O.; Ajayi, M. B.; Adekola, A. T.; Omole, A. I.; Akhigbe, R. E. (Frontiers in Nutrition, 2024)
Context Although the hypoglycaemic effect of Andrographis paniculata (Burm.f.) Nees [Acanthaceae] has been documented, reports on its effect in an apparently healthy state are limited. Objective This study investigated whether or not A. paniculata exerts hypoglycaemic effect in a non-diabetic state. It also explored the impact of A. paniculata on glycolytic enzymes and GLUT 4 protein expression, as a possible mode of action. Methods Twenty male Wistar rats were randomly assigned into two groups (n = 10 rats/group). The control rats were vehicle-treated (0.5 ml of distilled water), while the A. paniculata-treated rats had 500 mg/kg of A. paniculata per os once daily for 35 days. Results A. paniculata treatment led to improved insulin sensitivity evidenced by increased HOMA-β (88.08 ± 2.13 vs. 120.80 ± 1.52, p < 0.0001), HOMA-S (283.60 ± 8.82 vs. 300.50 ± 9.30, p = 0.0189), and reduced TyG index (4.22 ± 0.04 vs. 3.95 ± 0.07, p < 0.0002) and HOMA-IR (0.32 ± 0.01 vs. 0.25 ± 0.01, p < 0.0001) when compared with the control. It also improved glucose regulation as depicted by reduced fasting blood glucose (3.77 ± 0.10 vs. 3.24 ± 0.11, p < 0.0001) and glycated hemoglobin (HbA1c; 7.69 ± 1.15 vs. 5.95 ± 0.82, p = 0.0245), and atherogenic dyslipidaemia, including AIP (−0.12 ± 0.03 vs. −0.26 ± 0.03, p < 0.0001) and CRI-I (2.70 ± 0.29 vs. 1.84 ± 0.27, p < 0.0001). These findings were accompanied by enhanced hepatic and muscular redox state, increased activities of glycolytic enzymes, upregulated GLUT 4 (0.80 ± 0.27 vs. 6.20 ± 0.84, p < 0.0001), and increased circulating nitric oxide (5.45 ± 0.24 vs. 6.79 ± 0.33, p = 0.0002). Conclusion A. paniculata exerts positive effect on glucose metabolism and utilization by improving insulin sensitivity and upregulating the activities of glycolytic enzymes and GLUT 4 protein expression. This implies that A. paniculata may be beneficial in preventing insulin resistance and incident diabetes. Nonetheless, it should be used with caution to prevent hypoglycaemia in a non-diabetic state.